PRETREATMENT OF MILLET HUSK USING ALKALINE HYDROGEN PEROXIDE TO ENHANCE ENZYMATIC HYDROLYSIS FOR REDUCING SUGAR PRODUCTION (FUDMA JOURNAL OF SCIENCES, 2021)
The effectiveness of alkaline hydrogen peroxide as a suitable choice of pretreatment for the conversion of millet husk to reducing sugars using cellulase enzyme for hydrolysis and subsequent ethanol production was determined. The effects of three variables on reducing sugar production from millet husk were determined using one factor at a time (OFAT) method namely; peroxide concentration, pretreatment time and pretreatment temperature. From the results, it was observed that a significant (P
Keywords: pretreatment, cellulose, hydrolysis, optimization, millet husk, hydrogen peroxide